Classes and communities - Beteille, Andre (2007)
In the Indian context, classes and communities do not form interchangeable categories. Caste, a defining feature of the community in India, has been a vital socio-economic institution since historical times. But it is Indian politics, especially since post-independence, that has been shaped by competing communities and the ascendancy "acquired" by certain communities over the other. However, as this article suggests, the two categories are not wholly disparate; rather it is the middle class that has been largely responsible for spearheading the interests of their respective communities. A potent tool in this ascendancy has been the issue of "reservations". - Reproduced.
Keywords: Communities